Evaluasi Program Mengajar Di Sekolah Program MBKM Di Fakultas Ilmu Sosial Universitas Negeri Gorontalo - Usman, Fadli; Abdussamad, Juriko; Tantu, Romy (FISIP Universitas Tanjungpura, 2024)
The aim of this research is to find out how the evaluation of the implementation of the teaching program on the campus of the MBKM program at the Faculty of Social Sciences, Gorontalo State University, is seen from the aspects of determining the focus of the evaluation, preparing the design/evaluation stages, collecting information, analyzing and interpreting information, making reports, managing the evaluation (managing evaluation), and evaluation for evaluation. This research method uses a descriptive approach with qualitative data analysis. The data collection techniques used were observation, interviews, and documentation. Based on the results of field research, the evaluation of the implementation of the teaching program at the MBKM school program, Faculty of Social Sciences, Gorontalo State University, has been carried out in accordance with the guidelines applicable at the university level. In its implementation, the evaluation of the implementation of this program still encounters several problems, such as a lack of information needed to carry out the evaluation and a lack of management of program reports that serve as references for further program implementation. It can be concluded that the evaluation of the implementation of the teaching program at the MBKM school program at the Faculty of Social Sciences, Gorontalo State University still needs to adapt to existing provisions and standards. There are several things that need to be addressed and improved. Keywords: Policy Evaluation, School Teaching Program, MBKM